Interactive effects of fire and grazing on soil and forage nitrogen dynamics in a tallgrass prairie - Winstead, Amy (My University, 2026)
Fire and large herbivores are dominant regulators of nutrient cycling in tallgrass prairie ecosystems, yet their combined effects on soil nitrogen (N) dynamics and links to forage quality across heterogeneous landscapes remain incompletely resolved. This thesis examined how fire frequency, grazing, and landscape position interact to regulate N cycling, N retention, and plant–soil feedbacks in tallgrass prairie systems. Using long-term experimental watersheds at Konza Prairie Biological Station and additional cross-site comparisons, we quantified soil N pools, inorganic N availability (NH₄⁺, NO₃⁻), potentially mineralizable N (PMN), autoclavable citrate-extractable (ACE) protein, extracellular enzyme activities, and forage quality (N concentration) across burn intervals, grazing regimes, and topographic positions. Results show that fire and grazing regulate distinct but interacting components of the N cycle. Infrequent fire increased soil N accumulation and proteinaceous organic N pools, reflected in higher total N and ACE protein. In contrast, grazing enhanced N availability and turnover, increasing nitrate, PMN, and shifting microbial enzyme allocation toward carbon acquisition, indicative of reduced microbial N limitation. Grazing effects were strongest in upland soils, and also caused a notable accumulation of soil total N; shallow soil depth and preferential grazer use may have intensified responses. Forage quality mirrored soil N dynamics, with grazing and less frequent fire producing higher forage N concentrations and lower C:N ratios, reinforcing feedbacks between plant inputs and microbial processes. However, forage N feedbacks were expressed primarily later in the growing season, and were not detected synchronously across multiple sites, despite consistent grazing effects on soil microbial N availability, reflecting the importance of plant growth dynamics in regulating N availability to grazers. Overall, fire and grazing did not uniformly increase or decrease N pools; instead, they redistributed N among storage, mineralization, and biological demand pathways. Together, these findings demonstrate that N cycling in tallgrass prairie is governed by the integration of fire, grazing, and landscape heterogeneity. Rather than a single-direction response, fire frequency and grazing create a spatially structured mosaic of N availability and retention, with implications for grassland resilience, management, and soil health under changing environmental conditions.
Keywords: Nitrogen; Soil; Forage; Prairie; Nutrient cycling; Soil health